Odpowiedź :
[tex]a)\\(-5) + (-3)-(-8)+(-14) = -5-3+8-14 = -14\\\\b)\\0,25 + \frac{3}{4} = \frac{25}{100}+\frac{3}{4} = \frac{1}{4}+\frac{3}{4} = \frac{4}{4} = 1\\\\c)\\2,8 - \frac{3}{5} =\frac{28}{10}-\frac{3}{5} = \frac{14}{5}-\frac{3}{5} = \frac{11}{5} = 2\frac{1}{5} = 2,2\\\\d)\\0,8\cdot(-\frac{3}{8}) = \frac{8}{10}\cdot(-\frac{3}{8}) = -\frac{3}{10} = -0,3\\\\e)\\-3\frac{1}{5}:0,8 = -3,2:0,8 = -32:8 = -4\\\\f)\\3,4:1,7 + \frac{6}{7}\cdot(-2\frac{1}{3}) = 2+\frac{6}{7}\cdot(-\frac{7}{3}) =2-2 = 0[/tex]
[tex]g)\\0,15\cdot\frac{5}{6}-(0,8\cdot\frac{3}{5}-\frac{4}{5}):(-\frac{3}{2})=\frac{15}{100}\cdot\frac{5}{6}-(\frac{8}{10}\cdot\frac{3}{5}-\frac{4}{5}):(-\frac{3}{2}) =\\\\=\frac{3}{20}\cdot\frac{5}{6}-(\frac{4}{5}\cdot\frac{3}{5}-\frac{4}{5})\cdot(-\frac{2}{3}) = \frac{1}{8}-(\frac{12}{25}-\frac{20}{25})\cdot(-\frac{2}{3})=\frac{1}{8}-(-\frac{8}{25})\cdot(-\frac{2}{3})=\\\\=\frac{1}{8}-\frac{16}{75} =\frac{75}{300}- \frac{128}{600} = -\frac{53}{600}[/tex]